Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140039
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Chemoreception and Arterial Pressure Responses to Intermittent Hypoxia

Abstract: Carotid bodies are the principal peripheral chemoreceptors for detecting changes in arterial blood oxygen levels, and the resulting chemoreflex is a potent regulator of blood pressure. Recurrent apnea with intermittent hypoxia (IH) is a major clinical problem in adult humans and infants born preterm. Adult patients with recurrent apnea exhibit heightened sympathetic nerve activity and hypertension. Adults born preterm are predisposed to early onset of hypertension. Available evidence suggests that carotid body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 200 publications
(312 reference statements)
2
93
0
2
Order By: Relevance
“…Especially considering that at least 3 days of IH exposure are required to alter carotid body responses to hypoxia (Peng et al , 2003; Prabhakar et al , 2007), it is likely that only central (e.g. NTS) components of the chemoreflex mediate sympathetic responses to hAIHT (Mifflin et al , 2015; Prabhakar et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially considering that at least 3 days of IH exposure are required to alter carotid body responses to hypoxia (Peng et al , 2003; Prabhakar et al , 2007), it is likely that only central (e.g. NTS) components of the chemoreflex mediate sympathetic responses to hAIHT (Mifflin et al , 2015; Prabhakar et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in CIH conditioned rodents have identified that both free radicals and ROS generated in the carotid body and the chemoreflex neural arc mediate the carotid body responses to CIH, thereby, activating SNA (Peng et al , 2011; Peng et al , 2013; Prabhakar et al , 2015; Semenza & Prabhakar, 2015). Other animal studies have demonstrated that antioxidants reduce the efflux of catecholamines from the adrenal medulla (Kumar et al , 2006) and reduce the carotid body response to CIH (Peng et al , 2011; Peng et al , 2013; Peng et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that, in addition to severe, long-standing cyclical IH, the patient with OSA often presents with several additional confounding causes of cardiovascular morbidity such as obesity, diabetes, as well as intermittent sleep disruption, and exaggerated swings in intrathoracic pressure occurring repeatedly throughout the night. Nevertheless, animal studies that simulate the severity, frequency, and duty cycle of the OSA patient's nightly cyclical patterns of IH have shown key maladaptive contributions from IH alone (3,17,30,60,66,92).…”
Section: Maladaptive Cyclical Ihmentioning
confidence: 98%
“…The biological responses to IH may be adaptive, even "therapeutic," or maladaptive, depending on the severity of the hypoxemia, its frequency of occurrence, its duration, and, importantly, the "pattern" and timing of each of the HbO 2 desaturation/ resaturation cycles (3,60,67,92,106).…”
Section: Intermittent Hypoxiamentioning
confidence: 99%
“…Carotid bodies are the principal sensory organs for detecting changes in arterial blood O 2 levels, and the ensuing chemosensory reflex is a potent regulator of sympathetic tone and blood pressure (Fitzgerald and Lahiri 1986;Kumar and Prabhakar 2012). Several lines of evidence from sleep apnea patients and CIH-exposed rodents suggest that heightened carotid body chemosensory reflex contributes to sympathetic activation and hypertension caused by recurrent apnea (Kara et al 2003;Prabhakar et al 2015). …”
mentioning
confidence: 99%